Analysis of the Influence of the Utilization of Augmented Reality Technology on IKEA Planner on Purchase Decisions through the Technology Acceptance Model (TAM) Approach - Della Rahman Ramadhani; Astri Wulandari; Rahmat Hidayat (LP2M IAIN Palopo, 2026)
The development of digital technology has encouraged companies to present innovations that are able to improve the consumer experience in the purchasing decision-making process. One of the innovations that is growing is the use of Augmented Reality (AR) technology through IKEA Planner, which allows consumers to visualize the placement of furniture products virtually before making a purchase. This research seeks to explore the influence of the use of Augmented Reality technology in IKEA Planner on consumer purchase decisions using the Technology Acceptance Model (TAM) approach. The variables analyzed included Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Behavioral Intention to Use, and Purchase Decision. The study used a quantitative approach with a survey method of IKEA Planner users who met the research criteria. Data was collected through questionnaire dissemination and analyzed using statistical analysis techniques to test the relationship between variables according to the research model. The results show that the use of Augmented Reality technology through IKEA Planner has a positive influence on purchasing decisions. The perception of usability, the perception of ease of use, attitude towards use, and the intention to use technology contribute to increasing consumer confidence in the purchase decision-making process. The findings of this study show that the application of Augmented Reality technology not only improves the digital shopping experience, but also becomes a marketing strategy that is able to strengthen consumer trust and support increased purchasing decisions. This research is expected to be a reference for companies in developing technology-based digital marketing strategies that are oriented towards improving consumer experience and behavior.